Meta-Analisis Pengaruh Penggunaan Laboratorium Virtual Untuk Meningkatkan Pemahaman Konsep Fisika - Rosdiana Rosdiana; Farid Nasihin Jamalsari; Yoga Budi Bhakti (Universitas PGRI Semarang, 2020)
Learning physics with practicum activities can create active learning. However, not all practicum can be done in real time. In the era of technological advancement and information practical activities can be done virtually. This research aims to analyze the influence of virtual laboratory use in improving physics learning outcomes. This research uses meta-analysis methods. Research begins by formulating research problems, then continues by using relevant research results for analysis. Data collection is done by searching electronic journals through Google Scholar. From the search it obtained research data sources from ten articles. Data analysis is done in a qualitative descriptive way. Based on the results of the analysis can be known that the application of virtual laboratories can improve the understanding of the concept of student physics.